A Participatory Governance Model for Community Based Waste Management to Enhance Legal Compliance and Public Social Welfare - Rengga Kusuma Putra; Lita Tyesta Addy Listya Wardhani; Edvardas Juchnevicius (Green Social: International Journal of Law and Civil Affairs, 2025)
This research explores the development of a participatory governance model for community based waste management systems, aiming to enhance both legal compliance and public social welfare outcomes. Community based waste management (CBWM) plays a critical role in addressing environmental and health challenges, yet its success is often hindered by weak governance structures, limited community involvement, and insufficient regulatory frameworks. The study introduces a governance model that integrates local community participation into decision making processes, encouraging ownership and responsibility among residents. The primary goal is to improve compliance with environmental regulations while promoting social welfare by fostering better public health and community cohesion. A review of literature highlights key theories of participatory governance, focusing on its ability to enhance legal adherence and increase social equity. Previous studies on CBWM demonstrate the potential of community involvement in overcoming barriers to legal compliance, such as weak enforcement and fragmented governance. However, challenges like inadequate infrastructure, socio economic factors, and cultural habits still impede full participation and compliance. The study utilizes a mixed methods approach, including stakeholder analysis, participatory workshops, and regulatory compliance assessments, to evaluate the effectiveness of the model. The results show that communities involved in participatory governance exhibit higher compliance with waste management laws, improved sanitation, and healthier living conditions. Furthermore, the model fosters social capital and community empowerment, contributing to long term sustainability. In comparison to centralized waste management systems, the participatory approach is found to be more adaptable, accountable, and socially accepted. While the model presents several benefits, challenges such as infrastructure limitations and cultural barriers remain. Future research should further investigate how to address these challenges, particularly through technological integration and cross sector collaborations, to ensure the scalability and sustainability of the participatory governance model.